1995
DOI: 10.1108/02656719510101178
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of some major quality awards

Abstract: Searching for quantitative tools to monitor the attainment of TQM objectives, reviews the Japanese, European and American quality awards and discusses their significance to business. The procedures, assessment criteria and benefits of the Deming Application Prize (DP), European Quality Award (EQA) and Malcolm Baldrige Quality Awards (MB) are examined in some detail and compared against each other. It has been found that the DP focuses on the dissemination of company wide quality control, continuous improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 4 publications
1
57
0
7
Order By: Relevance
“…In recent years quality award programs such as the European Quality Award [19] and the Malcolm Baldrige Award (MBNQA) [20], have brought attention to quality issues and helped to clarify the meaning and the key constituents of quality management [21,22]. After comparing the key elements included in our TQM definition with the building blocks of the EFQM and MBNQA frameworks (see Table 1) we can conclude that, as a whole, the TQM definition used in this study is consistent with EFQM and MBNQA frameworks.…”
mentioning
confidence: 99%
“…In recent years quality award programs such as the European Quality Award [19] and the Malcolm Baldrige Award (MBNQA) [20], have brought attention to quality issues and helped to clarify the meaning and the key constituents of quality management [21,22]. After comparing the key elements included in our TQM definition with the building blocks of the EFQM and MBNQA frameworks (see Table 1) we can conclude that, as a whole, the TQM definition used in this study is consistent with EFQM and MBNQA frameworks.…”
mentioning
confidence: 99%
“…Ao estudar os prêmios MBNQA (americano), Deming Prize (japonês) e EQA (europeu), Bohoris (1995) verificou que cada uma dessas premiações apresenta um modelo próprio, composto por um conjunto de critérios de avaliação que diferem em termos de: propósitos; valores e conceitos; e em suas orientações para a implementação do TQM. E que a grande diferença existente entre o Prêmio Deming e os demais é que este não inclui determinados critérios, como: avaliação da gestão de recursos humanos, resultados da satisfação do cliente, impacto na sociedade e resultados operacionais.…”
Section: Artigos Com Foco Na Comparação Dos Prêmiosunclassified
“…Segundo Sharma e Talwar (2007), Miguel, Morini e Pires (2004), Miguel (2001), Goobadian e Woo (1996), Laszlo (1996), Izadi, Kashef e Stadt (1996) e Bohoris (1995), os mais conhecidos destes prêmios são: Deming Prize (Japão) (UNION. Na busca da excelência, empresas utilizam os modelos de excelência em gestão preconizados por tais prêmios para definir suas ações.…”
Section: Introductionunclassified
“…Several studies reported that the most frequently cited reason given for failure was a neglect of the organizational culture. Many organizations have already realized that their only way of surviving in today's competitive global market is to become a successful "total quality organization" [10]. Related to that, the significant association between TQM activities and organizational competitiveness has been noted [11].…”
Section: Collaboration Concept and Tqmmentioning
confidence: 99%